2002
DOI: 10.1523/jneurosci.22-24-11019.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Signal-to-Noise Ratio and Phase Locking for Small Inputs by a Low-Threshold Outward Current in Auditory Neurons

Abstract: Neurons possess multiple voltage-dependent conductances specific for their function. To investigate how low-threshold outward currents improve the detection of small signals in a noisy background, we recorded from gerbil medial superior olivary (MSO) neurons in vitro. MSO neurons responded phasically, with a single spike to a step current injection. When bathed in dendrotoxin (DTX), most cells switched to tonic firing, suggesting that low-threshold potassium currents (I(KLT)) participated in shaping these phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
133
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 42 publications
21
133
1
Order By: Relevance
“…Previously, we studied experimentally (gerbil, in vitro slice preparation) how SNR and phase-locking are affected by low-threshold potassium currents in MSO neurons (Svirskis et al 2002), finding results similar to those in this paper. We also showed there using a Hodgkin-Huxley type model that a low-threshold potassium conductance, based on experimentally defined parameters, could account for the effects observed.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previously, we studied experimentally (gerbil, in vitro slice preparation) how SNR and phase-locking are affected by low-threshold potassium currents in MSO neurons (Svirskis et al 2002), finding results similar to those in this paper. We also showed there using a Hodgkin-Huxley type model that a low-threshold potassium conductance, based on experimentally defined parameters, could account for the effects observed.…”
Section: Discussionsupporting
confidence: 86%
“…We also showed there using a Hodgkin-Huxley type model that a low-threshold potassium conductance, based on experimentally defined parameters, could account for the effects observed. In this work, we used the LIF model enhanced with a time-dependent piecewise-linear membrane currentvoltage relation and showed that its response properties were qualitatively similar to those recorded experimentally and seen in a model with Hodgkin-Huxley type conductances (Svirskis et al 2002). This means that the minimal model captures a number of the essential firing and membrane properties of phasic auditory neurons.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition to those models of NL referred to above, there are related models of coincidence detection in mammalian medial superior olive (MSO), or models general enough to apply equally well to both MSO and NL (Colburn et al 1990;Han and Colburn 1993;Brughera et al 1995;Brand et al 2002;Colburn and Zhou 2002;Svirskis et al 2002;Svirskis and Rinzel 2003;Zhou and Colburn 2003). For a dated but valuable review, see Colburn (1996).…”
Section: Related Modelsmentioning
confidence: 99%